2017
DOI: 10.1007/s13304-017-0465-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor size and focality with recurrence/persistence in papillary thyroid cancer patients treated with total thyroidectomy along with radioactive-iodine ablation and TSH suppression

Abstract: Locoregional recurrence is common in papillary thyroid cancer PTC and an optimal surgical treatment with respect to the multifocal nature of the disease stays controversial. It is a retrospective analytical study design. 209 diagnosed PTCs managed at our institute were grouped into macro-PTC with a size of dominant focus >1 cm (unifocal n = 106 and multifocal n = 64) and micro-PTMC if size of all foci was <1 cm; (unifocal n = 16 and multifocal PTMC n = 23). The primary endpoint is recurrence and tumor free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Otherwise, some authors [36][37][38] have found tumour multifocality as an important prognostic factor for disease recurrence/persistence, although the cohort was different from our study since they included patients with intermediate and high risk. Similar to our results (although with different inclusion criteria), others found no association between multifocality and tumour recurrence [39,40].…”
Section: Discussionmentioning
confidence: 61%
“…Otherwise, some authors [36][37][38] have found tumour multifocality as an important prognostic factor for disease recurrence/persistence, although the cohort was different from our study since they included patients with intermediate and high risk. Similar to our results (although with different inclusion criteria), others found no association between multifocality and tumour recurrence [39,40].…”
Section: Discussionmentioning
confidence: 61%
“…Multifocality—Some studies indicated that multifocality is present in about 30–37% of PTC patients [ 83 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. However, whether it may represent an independent risk factor for disease recurrence and overall mortality is still a matter of debate, because different reports produced conflicting results [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 126 ]. In particular, in a large multicenter study performed on 2638 PTC patients, multifocality was not found to be an independent prognostic marker for either PTC recurrence or death [ 124 ].…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
“…Considering the high incidence of postoperative complications, the routine use of TT is not recommended for all patients with unilateral PTC. However, multifocal PTCs were reported to be associated with poor outcome, and increased risk of recurrence ( 7 , 12 , 13 ). High resolution of ultrasonography (US), which could detect foci as small as 2–3 mm, is currently used in detecting PTC and determining the scope of surgery ( 14 ).…”
Section: Introductionmentioning
confidence: 99%